Variation in Membrane Composition Associated with Body Mass and Body Temperature in Tropical and North American Bees - Rodríguez, Enrique (Université d'Ottawa / University of Ottawa, 2013)
Membrane diversity associated with variation in body mass and body temperature of hymenopterans was investigated. Body mass of organisms affects most aspects of their biology, including physiological traits. One trait influenced by mass is metabolic rate, but the basis for its variation among organisms remains unclear. Recent work revealed that membrane phospholipid composition varies systematically with body mass: smaller vertebrates with higher mass-specific metabolic rates have more fluid membranes containing more long chains of polyunsaturated fatty acids (PUFA) and less monounsaturated fatty acids (MUFA). This “membrane pacemaker” theory of metabolism has recently been challenged by a lack of link between metabolic rate and membrane composition. To test this relationship, we have quantified the membrane lipid composition of 22 species of Panamanian orchid bees with a 22-fold range in mass. Results incorporating phylogenetic analysis show significant relationships for 18:1 (MUFA) and 18:3 (PUFA) with body mass that are consistent with the “pacemaker” theory, and unexpected relationships with saturated fatty acids (SFA). Moreover, changes in membrane fatty acid composition with temperature are a strategy in ectothermic poïkilotherms that is part of the “homeoviscous adaptation” model. Here, we report systematic variations in fatty acid composition linked with thoracic temperature excess in North American Hymenopterans, a novel discovery in these heterotherms. These findings are discussed in the context of diet, metabolism and lifespan.
Keywords: Membrane; Lipids; Hymenopterans; Membrane pacemaker theory; Metabolic rate; Bees; Thorax temperature